The evaluation of pinhole glasses as visual therapy in improving refractive error - Che Arif, Fatin Amalina; Che Azemin, Mohd Zulfaezal (IIUM Press, 2019)
Introduction: Visual therapy or eye exercise, which is widely used in behavioral optometry, has been successfully helping some visual disorders, especially binocular vision problem. In Bates System of Eye Exercise, it is claimed that eye exercise can restore vision with refractive error by completely relaxing the eyes. One of the ways to relax the eyes is by wearing the pinhole glasses as the pinhole placed before the eyes will help to relax accommodation and temporarily improving vision by reducing the size of blur circle. Pinhole glasses have been marketed as a visual therapy device, with the claim that continuous use of these glasses will improve refractive error. Although only anecdotal evidences have been provided on the efficacy of this product, the society are still interested to use the pinhole glasses and believe that their vision could be improved by simply wearing this device. Aim: The purpose of this study was to compare the refractive error of myopic participants before and after wearing the pinhole glasses for 3 weeks. Methodology: Fifteen participants were recruited in this study and all of the participants wore the pinhole glasses while performing near works for 20 minutes/day, anytime from 9 p.m. to 11 p.m. everyday for 3 weeks. Results: The refractive error before and after the intervention was then being compared and the results showed that there was no significant difference in refractive error of both right (p= 0.08) and left eyes (p= 0.09) of myopic participants before and after wearing the pinhole glasses. Conclusion: Our results suggest that pinhole glasses did not improve the refractive error of myopic participants.